2020
DOI: 10.1002/pssa.201901014
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effective Green Synthesis of Boron‐Rich Carbide Coatings for Infrared Windows and Night‐Vision Optics

Abstract: The increasing demand for infrared (IR) window materials for various applications in optical imaging systems necessitates the development of cost‐effective green techniques. Herein, the synthesis of refractory boron carbide (BC) using castor oil, as carbon precursor, and the preparation of IR transparent films by thermal vapor deposition technique is reported. Films are prepared with 1:3, 1:4, and 1:5 ratios of boric acid and castor oil, respectively. The X‐ray diffraction (XRD) and Fourier‐transform IR (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[35] For a film of transmittance T, reflectance R, refractive index (n), and thickness t, then the absorption coefficient α can be expressed as Equation (3). [36] α…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] For a film of transmittance T, reflectance R, refractive index (n), and thickness t, then the absorption coefficient α can be expressed as Equation (3). [36] α…”
Section: Methodsmentioning
confidence: 99%
“…For a film of transmittance T , reflectance R , refractive index ( n ), and thickness t , then the absorption coefficient α can be expressed as Equation (3). [ 36 ] α=1t×lnTfalse(1Rfalse)2=4πkλwhere k is the extinction coefficient at wavelength λ. The complex refractive index n * = n – ik tells about the absorption or energy loss in the sample through the imaginary part and the change in wavelength due to wave propagation to another medium through the real part.…”
Section: Methodsmentioning
confidence: 99%
“…However, the recent fast-breaking technology innovation has stressed the rising necessity of IR detectors for various scientific and industrial applications such as health monitoring, artificial vision for robotics and autonomous cars, optical communication networks, advanced night vision, ultrahigh-resolution spectroscopy, biomedical imaging, etc. In particular, the short-wavelength infrared (SWIR) with a wavelength range of λ = 1400–3000 nm is one of the interesting IR portions because it is suitable for sensing a reflected radiation like visible light as well as thermal radiation emitted from hot sources over 100 °C typically and can penetrate deeper than a NIR light. Therefore, the SWIR light technology is being keenly engaged for the development of new light detection and ranging (LiDAR) sensors for better performances. , However, no study has been so far reported on OPTRs for the sensing of SWIR light.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of polymeric precursors enables control over the nal product's properties and structures by varying the precursor composition at low-temperatures [11,34,35]. Based on the above advantages of polymeric precursors, the bulk BC structure can be tailored to NWs by choosing the correct precursor ratio and suitable synthesis temperature.…”
Section: Introductionmentioning
confidence: 99%